Pengaruh Tepung Kunyit dalam Ransum terhadap Performa Pertumbuhan Itik Mojosari - Abdul Karim Djasman Lameo; Widiastuti Ardiansyah; Susan Mokoolang (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
Turmeric powder contains curcuminoids, essential oils, flavonoids, and phenolic compounds that may support digestive function and nutrient utilization in poultry. This study evaluated the effects of dietary turmeric powder levels on feed intake, body weight gain, feed conversion ratio, and mortality of male Mojosari ducks. A completely randomized design with four treatments and six replicates was used. The treatments consisted of diets containing 0%, 6%, 8%, and 10% turmeric powder. The ducks were reared for 30 days; feed was provided twice daily and drinking water was offered ad libitum. Data were analyzed by analysis of variance followed by Duncan’s multiple range test when significant effects were detected. Turmeric powder significantly affected feed intake, body weight gain, and feed conversion ratio (P<0.01), but did not significantly affect mortality (P>0.05). The 10% treatment produced the highest feed intake (55.44 g/bird/day) and body weight gain (563.20 g/bird), the lowest feed conversion ratio (10.14), and the lowest numerical mortality (2%). Thus, 10% turmeric powder produced the best performance among the tested levels. However, feed formulation, nutrient composition, animal number, and feed conversion calculations should be verified before broader application.